Skrining dan evaluasi aktivitas kitinase dari sembilan isolat bakteri lokal - Maggadani, Baitha Palanggatan; Setyahadi S, Siswa; Harmita, Harmita (UI Scholars Hub, 2017)
Chitinase is an enzyme that degrades chitin on β-1,4-acetamido-2-deoxy-D-glycoside bound to produce Chitin oligosaccharide or its soluble monomer, N-acetylglucosamine (NAG). Chitinase are usually produced naturally by chitinolytic microorganism that are found in soil or water environment. Chitinase have been widely used for biocontrol agents of plant pests. The product from chitinase hydrolysis can be used as antiinflammatory agent and anti hyperpigmentation. This research was aimed to screen and evaluate the chitinolytic ability of 9 isolate. The best isolate was the one which produced high chitinolytic activity and hydrolyzed chitin into NAG. 9 isolate were examined and BPPTCC-2 was the best isolate which produced highest level of chitinolytic activity 0.1780 U/ml. The chitinase was able to hydrolyzed chitin resulting high yields of NAG 11.5% as the only product.